1995
DOI: 10.1108/02656719510076258
|View full text |Cite
|
Sign up to set email alerts
|

Selection of TQM pilot projects using an MCDM approach

Abstract: BackgroundSagging domestic and global market shares in key industries in the early 1980s and subsequent analysis of Japanese manufacturing practices [1,2] prompted US companies to formulate a conscious quality management strategy. This led to the total quality management (TQM) revolution in the late 1980s. To improve the quality of goods and services of US companies, Congress established the Malcolm Baldrige Award in 1987. The Baldrige Award has generated a very strong and lasting wave of interest by many US b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
0
33
0
5
Order By: Relevance
“…Ahire and Rana (1995) proposed an MCDM model using AHP to identify and to select key pilot of Total Quality Management (TQM) projects and worked on developing it. This model helps organizations prioritize and enhance the returns from TQM efforts applied to a hospital environment.…”
Section: Ahp Fuzzy Ahp Anp and Fuzzy Anpmentioning
confidence: 99%
“…Ahire and Rana (1995) proposed an MCDM model using AHP to identify and to select key pilot of Total Quality Management (TQM) projects and worked on developing it. This model helps organizations prioritize and enhance the returns from TQM efforts applied to a hospital environment.…”
Section: Ahp Fuzzy Ahp Anp and Fuzzy Anpmentioning
confidence: 99%
“…Central to these is the requirement that for TQM to take root successfully in the longterm, it must have a positive influence not only on employees' behaviour, but also on their attitudes and values. Ahire and Rana [1] proposed that as with any new concept, the extent to which TQM will be successful in any organisation is determined by its initial impact and its perceived worth as a new way of operating. According to Ahire and Rana [1], the literature dealing with participative decision making and organisational dynamics points to the fact that any new technical or management approach is either accepted sincerely or rejected based on the first few experiences with it.…”
Section: Importance Of Implementation Processmentioning
confidence: 99%
“…[15]. 1 For example, the ABI Inform CD-ROM Database, which provides citations of articles in a large and diverse number of journals dealing with management-related issues, revealed that between January 1986 and December 1991 a total of 407 articles were referenced. Between January 1992 and December 1995 the number of articles referenced was 2281 -a significant increase in volume.…”
Section: Importance Of Implementation Processmentioning
confidence: 99%
See 2 more Smart Citations